Cochrane Database of Systematic Reviews 2009
DOI: 10.1002/14651858.cd006282.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Drug treatment for spinal muscular atrophy types II and III

Abstract: BackgroundSpinal muscular atrophy (SMA) is caused by a homozygous deletion of the survival motor neuron 1 (SMN1) gene on chromosome 5, or a heterozygous deletion in combination with a (point) mutation in the second SMN1 allele. This results in degeneration of anterior horn cells, which leads to progressive muscle weakness. Children with SMA type II do not develop the ability to walk without support and have a shortened life expectancy, whereas children with SMA type III develop the ability to walk and have a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 159 publications
0
5
0
Order By: Relevance
“…Until recently no drug treatment had proved to be able to influence the disease course of SMA. A Cochrane review published in 2012 reported six randomized placebo-controlled trials on treatment for SMA using creatine, phenylbutyrate, gabapentin, thyrotropin-releasing hormone, hydroxyurea and combination therapy with valproate and acetyl-L-carnitine [36,37]. None of these studies showed statistically significant effects on the outcome measures in participants with SMA types 2 and 3.…”
Section: Medication Supplements and Immunizationsmentioning
confidence: 99%
“…Until recently no drug treatment had proved to be able to influence the disease course of SMA. A Cochrane review published in 2012 reported six randomized placebo-controlled trials on treatment for SMA using creatine, phenylbutyrate, gabapentin, thyrotropin-releasing hormone, hydroxyurea and combination therapy with valproate and acetyl-L-carnitine [36,37]. None of these studies showed statistically significant effects on the outcome measures in participants with SMA types 2 and 3.…”
Section: Medication Supplements and Immunizationsmentioning
confidence: 99%
“…Thus it has been proposed that preventing muscle atrophy could ameliorate the symptoms of muscle weakness in SMA patients [21]. Clinical trials with creatine, phenylbutryate, gabapentin and thyrotropin releasing hormone in type II and III SMA patients showed no significant effect on the disease course [22]. Delivery of follistatin, a negative regulator of muscle growth, improved the muscle mass but had no increase in maximium survival in SMA mice [23].…”
Section: Introductionmentioning
confidence: 99%
“…The potential drugs include histone deacetylase (HDAC) inhibitors such as sodium butyrate [ 41 ], phenylbutyrate [ 42 ], valproic acid (VPA) [ 43 ], trichostatin A [ 44 ], SAHA [ 45 ], and LBH589 [ 46 ], as well as hydroxyuria [ 47 ], sodium vanadate [ 48 ], aclarubicin [ 49 ], indoprofen [ 50 ], bortezomib [ 51 ], and aminoglycosides, such as tobramycin, amikacin [ 52 ], TC007 [ 53 ], and G418 [ 54 ]. Since there are still no drugs that have shown consistent benefits in clinical trials [ 55 , 56 ], finding an effective treatment with distinct therapeutic mechanisms, such as SMN independent targets, is necessary for future SMA therapy.…”
Section: Smn Dependent Therapymentioning
confidence: 99%
“…However, another clinical trial which enrolled 120 type II and III SMA patients showed a significant improvement in muscle strength of legs at both 6 and 12 months after gabapentin treatment [ 114 ]. Meta-analysis of these two trials did not successfully demonstrate the beneficial effects of gabapentin in SMA [ 56 ].…”
Section: Smn Independent Targets and Treatmentmentioning
confidence: 99%